Zambian Mole-Rats: 33 Years on the Scene and What We Still Do Not Know and How We Could Learn It - Hynek Burda (Frontiers in Ecology and Evolution, 2022)
This article surveys more than three decades of research on Zambian mole-rats (genus Fukomys, Bathyergidae), pointing out some unanswered questions and untested hypotheses and suggesting approaches to address them. These research proposals range from sensory ecology topics, the main research field, covering different (even not yet identified) senses, orientation in time and space, communication, studies on aging, population dynamics, and the survival strategies of mole-rats during yearly floodings in the Kafue Flats. Discussion includes cryptozoological investigation into the existence of strange mole-rat species in some Zambian localities as reported by local communities, the study of mole-rats in assumed contact (hybrid?) zones of special interest, (cyto)genetic studies of hybrids of selected species, and a non-invasive study of population and family structure and dynamics with help of endoscopes. In each case, there is a rationale, reasoning, hypothesis, and suggested methodical approach.